Proxy re-encryption architect for storing and sharing of cloud contents. Issue 3 (3rd May 2020) - Rawal, Bharat S.
ABSTRACT: Internet-based online cloud services provide enormous volumes of storage space, tailor-made computing resources and eradicate the obligation of native machines for data maintenance as well. Cloud storage service providers claim to offer the ability of secure and elastic data-storage services that can adapt to various storage necessities. Most of the security tools have a finite rate of failure, and intrusion comes with more complex and sophisticated techniques; the security failure rates are skyrocketing. Once we upload our data into the cloud, we lose control of our data, which certainly carries new security hazards toward integrity and privacy of our information. In this paper, we discuss a secure file sharing mechanism for the cloud with proxy re-encryption (PRE). PRE-scheme is implemented with the Disintegration Protocol to secure storage data in storage and in the flight. The paper introduces a new contribution of a seamless file sharing technique among different clouds without sharing an encryption key. Graphical Abstract: